Henoch-Schönlein Nephritis Manifesting with Purpura 15 years after Diagnosis of IgA Nephropathy - Hideaki Yamabe; Mitsuaki Kaizuka; Satoru Tsunoda; Tasuku Nagasawa; Kazuo Nomura; Michiko Shimada (Case Reports in Nephrology)
Henoch-Schönlein nephritis or immunoglobulin A (IgA) vasculitis is characterized by purpura, arthralgia, abdominal pain, and glomerulonephritis with glomerular IgA deposition. Notably, the presence of purpura is essential to diagnose this disease. We report the case of a patient in whom proteinuria and haematuria were detected during screening tests and he was diagnosed with IgA nephropathy at 20 years of age. Corticosteroids were administered for 7 years and were subsequently tapered. At 35 years of age, he noticed purpura on his lower extremities and was diagnosed with anaphylactoid purpura. Following the appearance of purpura, urinalysis revealed an increase in urinary protein levels from 0.7 g/g creatinine (Cr) to 1.4 g/gCr, and his serum Cr levels increased from 1.1 mg/dL to 1.35 mg/dL. Two months later purpura subsided, and his urinary protein level and serum Cr level were restored to the former levels. Although the cause remains unknown, an interval may occasionally be observed between the appearance of purpura and urinary abnormalities. However, to our knowledge to date, a 15-year interval is the longest interval, in such cases, reported in the literature.